2020
DOI: 10.1186/s13046-020-01631-w
|View full text |Cite
|
Sign up to set email alerts
|

Human umbilical cord mesenchymal stem cells-derived exosomes deliver microRNA-375 to downregulate ENAH and thus retard esophageal squamous cell carcinoma progression

Abstract: Background: Exosomal microRNAs (miRNAs or miRs) from bone marrow-derived mesenchymal stem cells (UCMSCs) have emerged as promising therapeutic strategies for cancer treatment. The current study aimed to elucidate the underlying mechanism of human umbilical cord mesenchymal stem cells (hUCMSCs)-derived exosomal miR-375 in esophageal squamous cell carcinoma (ESCC). Methods: After determining the expression of miR-375 and its putative target enabled homolog (ENAH) in ESCC tissues and cells, we tested effects of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 41 publications
1
41
0
Order By: Relevance
“…Exosomes secreted from HeLa cells can destroy endothelial barriers to facilitate tumor metastasis by inducing endoplasmic reticulum stress in endothelial cells (52). Exosomal miR-375 has also been validated to serve as a communicator mediating the crosstalk between different cells in the tumor microenvironment, thus affected the biological functions of exosome-recipient cells such as tumor cells (31) and fibroblasts (30). In our research, we revealed that miR-375-3p was enwrapped into exosomes by SCLC cells and delivered to vascular endothelial cells, and this communication was visualized under a fluorescence microscope.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes secreted from HeLa cells can destroy endothelial barriers to facilitate tumor metastasis by inducing endoplasmic reticulum stress in endothelial cells (52). Exosomal miR-375 has also been validated to serve as a communicator mediating the crosstalk between different cells in the tumor microenvironment, thus affected the biological functions of exosome-recipient cells such as tumor cells (31) and fibroblasts (30). In our research, we revealed that miR-375-3p was enwrapped into exosomes by SCLC cells and delivered to vascular endothelial cells, and this communication was visualized under a fluorescence microscope.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, exosomal miR-375 secreted by Merkel cell carcinoma could induce fibroblast polarization to construct a pro-tumorigenic microenvironment by targeting RBPJ and p53 (30). Exosomal miR-375 derived from umbilical cord mesenchymal stem cells could inhibit esophageal squamous cell carcinoma progression via inhibiting ENAH (31). These researches underlined the importance of exosomal miR-375 in cell communications and tumor progressions, but its role in SCLC has never been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the existing literature, there is no “gold standard” exosomal miRNA or ideal endogenous molecule for RT-qPCR normalization in body fluids; some studies recommend spiked-in controls, i.e., Caenorhabditis elegans (cel)-miR-39 or cel-miR-54 ( 50 , 51 ). As a classical internal control, U6 is still used to normalize miRNA expression levels in blood or other fluids ( 52 54 ). In our study, we used U6 as an internal control, without spiked-in controls.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these technical and biological challenges facing this research field, another important concern should be taken in consideration regarding the potential protumoral function of MSC-EVs due to their contents of a spectrum of biological factors (e.g., IL-6) that can promote proliferation, angiogenic activity, and motility of cancer cells and foster the immunosuppressive and metastatic niches (DeNardo and Ruffell 2019; Ren et al 2019; Valenzuela Alvarez et al 2019). Interestingly, recent studies have shown that MSC-EVs inhibit angiogenesis, tumor growth, and progression in oral and esophageal squamous cell carcinoma (Rosenberger et al 2019; He et al 2020). According to these important findings, it is worthwhile to further explore the potential effects of GMSC-EVs on tumor growth, angiogenesis, and metastasis both in vitro and in vivo so as to guarantee the biosafety before translation into clinical studies.…”
Section: Discussionmentioning
confidence: 99%